Adaptation and Hybridisation of Commons in Aït Oucheg Territory, High Atlas, Morocco - Charles Bonnin; Elouarti Ayoub; Bruno Romagny; Michel Vaillant; Geneviève Michon; Saïd Boujrouf; Mohammed Aderghal (Revue de Géographie Alpine)
Since the years 2000, Morocco has seen a strong associative dynamic, in both urban and rural areas. In marginalised rural territories (mountains, oases, steppe, etc.), this infatuation for the associative phenomenon is in phase with two major factors : the partial disengagement of the State and a tendency towards the breakdown of collective action. It is in this context a priori unfavourable for the emergence of practices related to commoning that we present an example of the mutation of a traditional commons, and an innovative form of collective action at the scale of a mountain village situated near Marrakesh. In both cases, we analyse the modes of reproduction of the practice of commoning. Irrespective of the nature of the commons studied, innovations at both the operational and institutional levels are essential in order to encourage the maintenance of the territorial commons. These innovations often result in hybrid forms of commons marked by institutional pluralism and changes of the actors involved, in a shifting socio-economic climatic context. The functioning of the local development association at Tizi n’Oucheg is a perfect illustration of this necessity to innovate for the rehabilitation of commons, which here involves the shifting of the arenas for collective choice from a customary institution towards an associative body.